A case of catheter related bloodstream infection by Corynebacterium striatum. (2020) - Ge, Yanmei; Lu, Jingchuan; Feng, Shaozun; Ji, Wenli; Tong, Huacheng
Abstract: Background: C. striatum is an innocuous inhabitant of the normal human epithelial and mucosal surfaces. The C. striatum ´ s thogenic potential is increasingly recognized in our time. Methods: We present a rare case of CRBSI by C. striatum in a 57-yr-old male patient. The patient suffered from many basic diseases and was admitted to hospital of shock. Results: The patient finally died of septic shock caused by CRBSI due to multidrug-resistant C. striatum which responded neither to empiric nor to targeted treatment. Conclusions: C. striatum can cause CRBSI in immunocompromised patients when they were treated by intravenous catheters.